Myoepithelioma-like Hyalinizing Epithelioid Tumors of the Hand With Novel OGT-FOXO3 Fusions. (March 2020) - Lee, Jen-Chieh; Chou, Hsiu-Chu; Wang, Chung-Hsi; Chu, Ping-Yuan; Hsieh, Tsung-Han; Liu, Mei-Ling; Hsieh, Shu-Min; Liu, Yun-Ru; Kao, Yu-Chien
Abstract : Myoepithelial tumors of soft tissue are uncommon neoplasms characterized histologically by spindle to epithelioid cells arranged in cords, nests, and/or reticular pattern with chondromyxoid to hyaline stroma, and genetically by rearrangement involving EWSR1 (among other less common genes) in about half of the cases. The diagnosis often requires immunostaining to confirm myoepithelial differentiation, most importantly the expression of epithelial markers and S100 protein and/or GFAP. However, there are cases wherein the morphology is reminiscent of myoepithelial tumors, while the immunophenotype falls short. Here, we report 2 highly similar myoepithelioma-like tumors arising in the hands of young adults. Both tumors were well-demarcated and composed of alternating cellular areas with palely eosinophilic hyaline stroma and scattered acellular zones of densely eosinophilic collagen deposition. The tumor cells were mainly epithelioid cells and arranged in cords or small nests. Vacuolated cells encircling hyaline matrix globules were focally prominent. A minor component of nonhyaline fibrous nodular areas composed of bland spindle cells and rich vasculature was also observed. Perivascular concentric spindle cell proliferation and perivascular hyalinization were present in some areas. The tumor cells were positive for CD34 and epithelial membrane antigen (focal) by immunostaining, while largely negative for cytokeratin, S100, GFAP, p63, GLUT1, and claudin-1. By RNA sequencing, a novel OGT-FOXO3 fusion gene was identified in case 1 and confirmed by reverse transcription polymerase chain reaction and fluorescence in situ hybridization in both cases. Sharing the unusual clinicopathologic features and the novel fusion, these 2 cases probably represent a distinct tumor entity, whose relationship with myoepithelial tumors and tumorigenic mechanisms exerted by the OGT-FOXO3 fusion remain to be studied.